International positioning of the spanish psychology journals - Tortosa-Pérez, Macarena; Osca-Lluch, Julia; López-López, Wilson; Alfaro-Ferreres, Elisa (Anales de Psicología / Annals of Psychology, 2019)
We present the results of the analysis of the dissemination and circulation of the number of Spanish journals in different national and international databases. This is a study of the journals that contain the main bibliographic databases until the year 2017. The increase of the presence of Spanish psychology journals in the different databases is an indicator that determines the growth and maturity of this discipline and provides an interesting view of the scientific activity in psychology and its situation in the international context. It shows that state policies and positioning campaigns of universities, associations and schools play a key role in the internationalization and positioning.